Cigarette smoking among psychiatric patients in Brazil - Fabiana Cristina Ribeiro de Barros; Ana Paula Souto Melo; Francine Cournos; Mariângela Leal Cherchiglia; Eliane Rezende de Morais Peixoto; Mark Drew Crosland Guimarães (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
The aim of this study was to estimate tobacco smoking prevalence among psychiatric patients attended in care facilities in Brazil and assess associated factors. A cross-sectional multicenter study was conducted of psychiatric patients (N = 2,475) selected from 26 care facilities. Current and ex-smokers were compared to those who had never smoked. Odds ratios were estimated using logistic regression. The current and past smoking prevalence rates were 52.7% and 18.9%, respectively. Being male, aged 40 years or over, drug and alcohol use, unprotected sex and a history of physical violence were factors associated with both current and past smoking, while a low education level (≤ 8 years of schooling), history of homelessness, not practicing a religion, current or previous psychiatric hospitalization, and main psychiatric diagnosis substance use disorders, were factors only associated with current smoking. Tobacco smoking prevalence among this population was high and was higher than the rate in the general population. Appropriate interventions and smoking prevention policies should be incorporated into mental health services.